The Metal Scene and The Bible: Meaning, Accuracy, and Silence - Watts, Peter (Journal of religion and popular culture, 2017)
This article examines the question how should we understand the use of the Bible in the metal scene? In the first part, we explore the example of Black Sabbath against the backdrop of the use of the Bible in the band's contemporary society. We argue that the Bible had a particular role in the genesis of Heavy Metal through an-admittedly hazy-understanding of biblical morality shared between metal bands and their audiences. In the second part, we make a more controversial claim. Given that the shared cultural biblical understanding has changed, the metal scene is self-consciously inauthentic, and the metal scene qua metal scene is authentically inauthentic, we argue that where the Bible is used in metal, its meaning is distorted and even silenced.